The UK and Brexit – Environmental opportunity or disaster? - MACRORY, Richard (The Opole Studies in Administration and Law, 2021)
The environmental implications of the UK leaving the EU have yet to be fully realized, but the picture is by no means all negative. Initially, as far as possible, all EU environmental legislation continues to apply in the interests of regulatory certainty but divergences are beginning to emerge. Brexit has led to the proposed establishment of a new independent environmental watchdog, and the Government has committed itself to ambitious environmental goals. The Common Agricultural Policy will be replaced by financial schemes that will pay farmers only for public benefits, mainly concerning the environment. At the same time, a consequence of Brexit is that that the UK will see increasing divergencies in environmental law and policy within its devolved administrations.